Learning Transitions in Higher Education - Scott, David; Hughes, Gwyneth; Evans, Carol; Burke, Penny Jane; Walter, Catherine; Watson, David; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book draws on a study of student transitions in higher education institutions to both unpack the concept of a learning transition and develop pedagogic strategies to enable learners to develop their learning careers. This book provides an original perspective on teaching and learning in higher education.
Keywords: Education; Philosophy and social sciences; School management and organization; School administration; Educational sociology; Higher education; Education -- Philosophy; Education and sociology; Sociology, Educational; Education and state; Sociology of Education; Higher Education; Administration, Organization and Leadership; Education Policy; Educational Philosophy; Philosophy of Education